A Study on Yogic Intervention and Core Skill Proficiency in Female Adolescent Soccer Players - sharma , Taniya; sharma , Sunil; kumar , Manish (International Research Journal of Ayurveda & Yoga, 2025)
Background: The increasing participation of adolescent females in competitive soccer highlights the need for comprehensive training approaches that support both skill development and mental well-being. Core soccer skills such as dribbling and passing require not only physical coordination but also cognitive clarity and emotional stability – areas often challenged during adolescence. Yoga, with its integrative approach encompassing physical postures, breathing techniques, and meditation, has shown promise in enhancing neuromuscular control and psychological resilience yet remains underexplored within athletic training contexts for adolescent females.